Impact of Intrapartum Oral Azithromycin on the Acquired Macrolide Resistome of Infants' Nasopharynx: A Randomized Controlled Trial. (23rd May 2020) - Bojang, Abdoulie; Baines, Sarah L; Camara, Bully; Guerillot, Romain; Donovan, Liam; Marqués, Raquel Sánchez; Secka, Ousman; D'Alessandro, Umberto; Bottomley, Christian; Howden, Benjamin P; Roca, Anna
Abstract: In a post hoc analysis of samples from an intrapartum azithromycin randomized clinical trial, we found that children whose mothers had been treated with the drug had higher prevalence of macrolide-resistance genes msr(A) and ermC at 28 days but not at 12 months. The 2 genes were positively associated in the nasopharynx. Clinical Trials Registration: NCT1800942.